Extending V-model practices to support SRE to build Secure Web Application - Abdulrazeg, AA; Norwawi, NM; Basir, N (IEEE, 2024)
Technological advancements and rapid growth in the use of the Internet by the society have had a huge impact on information security. It has triggered the need for a major shift in the way web applications are developed. The high level security of these applications is crucial to their success. Therefore, information security has become a core requirement for producing trustworthy software driven by the need to guard critical assets. To develop a web application with adequate security features, it is highly recommended to capture security requirements early in the development lifecycle. In this paper, we propose a way of extending the V-Model requirements engineering phase to aid developers to engineer security requirements for a web application being developed, as well as, handling the security test planning. The aim is to support the proactive definition of security requirements by integrating security requirements engineering ( SRE) activities with requirements engineering ( RE) activities of the V-model.